Nannofossils, foraminifera and microforaminiferal linings in the Cenozoic diamictites of Cape Lamb, Vega Island, Antarctica - Concheyro, Graciela (2014)
Micropaleontological and palynological samples from three Cenozoic dia− mictites at Cape Lamb, Vega Island, James Ross Basin were analysed. Fossiliferous sam− ples yielded reworked and autochthonous assemblages of Mesozoic calcareous nanno− fossils, impoverished Cretaceous foraminifera together with Neogene species, as well as Late Cretaceous dinoflagellate cysts, pollen, spores and abundant Cenozoic micro− foraminiferal linings. The recovered nannoflora indicates Early Cretaceous (Hauteri− vian–Albian) and Late Cretaceous (Santonian–Early Campanian) ages, suggesting an in− tensive reworking of marine sediments. The presence of the Early Cretaceous species Nannoconus circularis Deres et Acheriteguy in the diamictite represents its first record for the James Ross Basin. The scarce foraminiferal fauna includes Pullenia jarvisi Cushman, which indicates reworking from lower Maastrichtian–lower Paleocene sedi− ments, and also the Neogene autochthonous Trochammina sp. aff. T. intermedia. The in− ner−organic layer observed inside this specimen appears to be identical to microfora− miniferal linings recovered from the same sample. Palynomorphs found in the studied samples suggest erosion from the underlying Snow Hill Island and the López de Berto− dano Formation beds (upper Campanian–upper Maastrichtian). These recovered assem− blages indicate either different periods of deposition or reworking from diverse sources during Cenozoic glaciation, originating in James Ross Island and the Antarctic Peninsula with the influence of local sediment sources.